PREMAN RECEH (PENGARUH MANTAN KOMBATAN GAM TERHADAP POLITIK DI TANAH RENCONG ACEH DI ERA OTSUS) - Sulfia Andika; Egi Saputra; Dista Setya Ningsih; Sarabila Sarabila; Alimas Jonsa (Universitas Teuku Umar, 2019)
Aceh as a special autonomous region according to the mandate contained in the Aceh Government Law (UUPA) No. 11 of 2006 which gives authority to Aceh,one of which can form a local party and regional regulations (qanun) themselves. The specificity of Aceh is the result of reconciliation between the Free Aceh Movement (GAM) and the Indonesian Government in an effort to resolve endless conflicts. After a conflict resolution effort is realized, to supervise and participate in carrying out the cousre of the UUPA the GAM ex-combatants are now participating in politics which is a better alternative in seeking justice and the rights of the people of Aceh. Therefore, this study aims to find out how much the influence of former GAM combatants on politics in Aceh and the indicators used to enter the political system in Aceh, especially in the districts of West Aceh and Nagan Raya. The methodology used in this study is the qualitative research methodology, with the descriptive approach expected in this study the results found are, in the form of conclusions and suggestions that can build both for former GAM combatants and for the community in their involvement in political implementation in Aceh. Keyword: Influence, Combatants, Aceh